Transcutaneous Auricular Vagus Nerve Stimulation Promotes White Matter Repair and Improves Dysphagia Symptoms in Cerebral Ischemia Model Rats - Long, Lu; Zang, Qianwen; Jia, Gongwei; Fan, Meng; Zhang, Liping; Qi, Yingqiang; Liu, Yilin; Yu, Lehua; Wang, Sanrong (Frontiers in Behavioral Neuroscience, 2022)
Abstract Background: Clinical and animal studies have shown that transcutaneous auricular vagus nerve stimulation (ta-VNS) exerts neuroprotection following cerebral ischaemia. Studies have revealed that white matter damage after ischemia is related to swallowing defects, and the degree of white matter damage is related to the severity of dysphagia. However, the effect of ta-VNS on dysphagia symptoms and white matter damage in dysphagic animals after ischaemic stroke has not been investigated. Methods: Middle cerebral artery occlusion (MCAO) rats were randomly divided into the sham, control and vagus nerve stimulation (VNS) group, which subsequently received ta-VNS for three weeks. The swallowing reflexes were measured once weekly by electromyography (EMG). White matter remyelination, volume, angiogenesis and the inflammatory response in the white matter were assessed by electron microscopy, immunohistochemistry, stereology, enzyme-linked immunosorbent assay (ELISA) and western blotting. Results: Ta-VNS significantly increased the number of swallows within 20 s and reduced the onset latency to the first swallow. ta-VNS significantly improved remyelination but did not alleviate white matter shrinkage after MCAO. Stereology revealed that ta-VNS significantly increased the density of capillaries and increased vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (FGF2) expression in the white matter. ta-VNS significantly alleviated the increase in TLR4, MyD88, phosphorylated MAPK and NF-κB protein levels and suppressed the expression of the proinflammatory factors IL-1β and TNF-α. Conclusion: These results indicated ta-VNS slightly improved dysphagia symptoms after ischaemic stroke, possibly by increasing remyelination, inducing angiogenesis and inhibiting the inflammatory response in the white matter of cerebral ischaemia model rats, implying that ta-VNS may be an effective therapeutic strategy for the treatment of dysphagia after ischaemic stroke.